Loss of heterozygosity on chromosome 11 q in breast cancer. - Tomlinson, I; Strickland, J; Lee, A; Bromley, L; Evans, M; Morton, J; McGee, J (1995)
AIMS: Chromosome 11q23 seems to be a site of frequent mutation in cancer. It also contains loci such as ataxia telangiectasia with possible importance in the pathogenesis of breast tumours. The short arm of chromosome 11 has been studied extensively in breast cancer, but the long arm, in particular the distal part, has been studied less frequently. Cytogenetic analysis has shown possible involvement of chromosome 11q in breast tumours. Chromosome transfer experiments have also implicated chromosome 11q in breast cancer. A high frequency of mutations might therefore be expected to occur on chromosome 11q in breast cancers. METHODS: Using restriction fragment analysis, the primary tumours of 41 patients with breast cancer were screened for mutations at five loci on chromosome 11q (D11Z1, INT2, (FGF3), DRD2, NCAM, and D11S29). RESULTS: Allelic loss occurred at a high frequency (59%) at D11S29. At NCAM, novel alleles were frequently seen on autoradiographs. Relatively low frequencies of mutation were detected at the other loci. Allelic loss at D11S29 was associated with the presence of lymph node metastases, but this may be a chance association. CONCLUSIONS: The frequency of allelic loss at the DS11S29 locus is high. The significance of novel alleles at NCAM and their relation to allelic loss at D11S29 are unclear. The results presented here do not permit fine mapping of a region of allelic loss, but suggest that the region of greatest loss lies distal to DRD2. The results provide further evidence for the importance of gene(s) near 11q23 in the pathogenesis of breast cancer, and of tumours in general.